Respostas
respondido por:
1
x^2+6x+9=0
delta= 6^2-4*1*9
36-36
delta=0
se delta é igual a 0, terá apenas uma raiz... (x' e x" são iguais)
(-b+-raiz de delta)/2a
(-6+-raiz de 0)/2*1
(-6+-0)/2
x' e x" = -6/2 = -3
delta= 6^2-4*1*9
36-36
delta=0
se delta é igual a 0, terá apenas uma raiz... (x' e x" são iguais)
(-b+-raiz de delta)/2a
(-6+-raiz de 0)/2*1
(-6+-0)/2
x' e x" = -6/2 = -3
BrunoOliveira111:
obrigado
respondido por:
1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás